Deep Trade Agreements and Vertical FDI : The Devil Is in the Details - Osnago, Alberto; Rocha, Nadia; Ruta, Michele (World Bank, Washington, DC, 2015)
Recent data show that the institutional content of preferential trade agreements has evolved over time. Although pre-1990s preferential trade agreements mostly focused on tariff liberalization, recent agreements increasingly contain deep provisions in diverse areas, such as intellectual property rights, investment, and standards. At the same time, there has been a remarkable increase in the internationalization of production through foreign direct investment and outsourcing. This paper employs the Antràs and Helpman (2008) model of contractual frictions and global sourcing to study how deep trade agreements affect the international organization of production. The paper constructs new measures of the depth of preferential trade agreements and of vertical foreign direct investment to test the theory. Consistent with the model, the analysis finds evidence that the depth of trade agreements is correlated with vertical foreign direct investment, and that this is driven by the provisions that improve the contractibility of inputs provided by suppliers, such as regulatory provisions. Because this implication of the model is specific to the so-called “property rights” theory of the multinational firm, the findings provide empirical support to this approach vis-à-vis alternative theories of firm boundaries.